The effects of peer education on treatment adherence among patients receiving hemodialysis: A randomized controlled trial - Alireza Irajpour; Maryam Sadat Hashemi; Parvaneh Abazari; Shahrazad Shahidi (Wolters Kluwer Medknow Publications, 2024)
Background: Non-adherence to treatments increases the rates of hemodialysis complications, hospitalization, and mortality. One strategy for adherence improvement is peer education. This study aimed to investigate the effects of peer education on treatment adherence among patients receiving hemodialysis. Materials and Methods: This was a randomized controlled trial. Patients in the control group were provided just with routine care, and the intervention group received peer education. Treatment adherence was assessed both before and after the intervention via the End-Stage Renal Disease (ESRD) Adherence Questionnaire. Data analysis was conducted by the Chi-square, the Mann-Whitney U, the paired-sample t, and the independent-sample t tests. Results: There were no significant between-group differences in terms of the pre-test mean scores of Adherence to regular attendance at hemodialysis sessions (t = 0.19, p = 0.85), Adherence to the prescribed medications (t = 0.46, p = 0.64), and Adherence to fluid restrictions (t = 0.24, p = 0.81). The same finding was observed after the intervention, except for the mean score of the adherence to fluid restrictions dimension which was significantly greater in the intervention group (t = 2.86, p = 0.006). Moreover, no significant changes were observed in the mean scores of treatment adherence dimensions in the control group. However, in the intervention group, the mean scores of the adherence to regular attendance at hemodialysis sessions (t = 3.79, p < 0.001) and the adherence to fluid restrictions dimensions were significantly greater than their pre-test values (t = 4.47, p < 0.001). Conclusions: Education by peer groups improves the compliance of patients with regard to the consumption of fluids in the interval between two dialysis sessions.